An Act to Amend and Reduce into one Act, the Several Laws for Regulating and Disciplining the Militia, 1785 Va. Acts ch. 1, § III, p 2 - (:unkn) unknown (My University, 1785)
Required members of the militia to keep arms, ammunition, and accoutrements ready when called for by their commanding officer.
Keywords: ARMED FORCES